PERANCANGAN FILM DOKUMENTER WISATA ALAM AIR TERJUN NYARAI LUBUK ALUNG PADANG PARIAMAN - HENDRO SAPUTRA, Hendra Afriwan, S.Sn., M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Nyarai Waterfall is one the tourism object that is located in Lubuk Alung, Padang Pariaman regency. To enter this tourist site, the visitors have to tracking in Gamaran Forest, Lubuk Alung. During the journey, the visitors will be given the wonderfull scenery to take a picture and also the visitors can take a rest on the road. The promotion that has been done by the organizer and goverment does not catch the audience target yet. As the result, it is important to make a media promotion such as documentary film to give an ilustration of the atmosphere as long as the journey to reach the location of  Nyarai waterfall. In addition, it will be provide by some another media to help the main media to promote this subject to audiences, like billboard, CD cover and CD label, T-Shirt, X-Banner, pin, stickers and buff and the drink bottle.This documentary film aimed to give information to audience target to feel the sensation of the journey to reach the location of Nyarai waterfall in Lubuk Alung. This film describe about the road about the beginning untill finished. Also, all of the rute will be ilustrate in this documentary film.The method that used in this study is SWOT analysis as the basic concepts to solve the problem. SWOT analysis is discuss about the strength, weakness, opportunities, and threats. The purpose of SWOT analysis is to give the ilustration of the findings. This analysis is used as the basic concept in arranging the objective and the planning strategies. Then, the aspects which is included in Nyarai waterfal tourism object can be combined in to documentary film. The documentary film of Nyarai Waterfall can be efective and communicative media.